Liver Graft-to-Spleen Volume Ratio as a Useful Predictive Factor of the Outcomes in Living Donor Liver Transplantation: A Retrospective Study - Xiao, Fei; Wei, Lin; Qu, Wei; Zeng, Zhi-Gui; Sun, Li-Ying; Liu, Ying; Zhang, Hai-Ming; Tan, Yu-Le; Wang, Jun; Zhu, Zhi-Jun (Frontiers in Surgery, 2022)
Background: In living donor liver transplantation(LDLT), graft-to-recipient weight ratio(GRWR)＜0.8% is an important index predicted portal hypertension, which may induce the graft small for size syndrome(SFSS). Recently, the value of graft-to-spleen volume ratio(GSVR) on predicted portal hypertension had been reported, whether without splenectomy prevent portal hypertension in transplantation remains disputed, we aimed to identify GSVR contributing to portal venous pressure (PVP) and outcomes without simultaneous splenectomy in LDLT. Methods: A retrospective study had been designed. Excluded patients with splenectomy,246 recipients with LDLT between 2016 and 2020 were categorized into a low GSVR group and a normal GSVR group. Preoperative, intraoperative, and postoperative data were collected, then we explored different GSVR values contributing to portal hypertension after reperfusion. Results: According to the 1st quartile of the distributed data, two groups were attached: low GSVR (＜1.03g/mL) and normal GSVR (>1.03g/mL). For the donors, there were significant differences in donor age, graft type, liver size, GRWR, and GSVR (P<0.05). Following the surgical factors, there were significant differences in blood loss and CRBC transfusion(P<0.05). The low GSVR has demonstrated had a significant relationship with ascites drainage and portal venous flow after LDLT(P<0.05). Meanwhile, low GSVR heralds worse results which covered platelet count, international normalized ratio (INR), and portal venous velocity(PVV). Kaplan-Meier analysis shows that there was a significant difference between the two groups, while the low GSVR group demonstrated worse recipients survival compared with the normal GSVR group (P<0.05). Conclusions: Without splenectomy, low GSVR was an important predictor of portal hypertension and impaired graft function after LDLT.